Effect of Asset Structure, Company Size, Liquidity, Profitability, and Sales Growth on Capital Structure - Heliani; Nur Hidayah K Fadhillah (Universitas Nusa Putra, 2022)
Errors in determining the capital structure can affect the sustainable development of a company which can increase the company's financial risk, namely if the company is unable to pay its interest expense and debt budget. This study was conducted to analyze the effect of Asset Structure, Firm Size, Liquidity, Profitability, and Sales Growth on Capital Structure in the Pharmaceutical Industry listed on the Indonesia Stock Exchange in 2016-2020. This type of research is quantitative with data obtained from financial statements. The population of this study is all pharmaceutical companies listed on the IDX. The sample was selected by purposive sampling and then 9 companies were selected as samples which were analyzed using Multiple Linear Regression Analysis. The results showed that the size of the company and profitability partially affect the capital structure. Meanwhile, the variables of Asset Structure, Liquidity, and Sales Growth partially do not affect Capital Structure. Simultaneously Asset Structure, Company Size, Liquidity, Profitability, and Sales Growth affect the Capital Structure.